Direct interaction of the molecular chaperone GRP78/BiP with the Newcastle disease virus hemagglutinin-neuraminidase protein plays a vital role in viral attachment to and infection of culture cells - Han, Chenxin; Xie, Ziwei; Lv, Yadi; Liu, Dingxiang; Chen, Ruiai (Frontiers in Immunology, 2023)
Glucose Regulated Proteins/Binding protein (GRP78/Bip), a representative molecular chaperone, effectively influences and actively participates in the replication processes of many viruses. Little is known, however, about the functional involvement of GRP78 in the replication of Newcastle disease virus (NDV) and the underlying mechanisms. The objectives of this study are to establish protein interactomes between host cell proteins and the NDV Hemagglutinin-neuraminidase (HN) protein, and to systematically investigate the regulatory role of the GRP78-HN protein interaction during the NDV replication cycle. Our study revealed that GRP78 is upregulated during NDV infection, and its direct interaction with HN is mediated by the N-terminal 326 amino acid region. Knockdown of GRP78 by small interfering RNAs (siRNAs) significantly suppressed NDV infection and replication. Conversely, overexpression of GRP78 resulted in a significant increase in NDV replication, demonstrating its role as a positive regulator in the NDV replication cycle. We further showed that the direct interaction between GRP78 and HN protein enhanced the attachment of NDV to cells, and masking of GRP78 expressed on the cell surface with specific polyclonal antibodies (pAbs) inhibited NDV attachment and replication.These findings highlight the essential role of GRP78 in the adsorption stage during the NDV infection cycle, and, importantly, identify the critical domain required for GRP78-HN interaction, providing novel insights into the molecular mechanisms involved in NDV replication and infection.